Expression analysis of GmNAC085 gene under dehydration and salt treatment in drought-tolerant DT51 and drought-sensitive MTD720 soybean cultivars - Hiếu, Đoàn Ngọc; Thư, Nguyễn Bình Anh; Xuân, Hoàng Thị Lan; Uyên, Nguyễn Phạm Kim; Thảo, Nguyễn Phương (Vietnam Journal of Biotechnology, 2016)
NAC transcription factors (NAC TFs) are important regulatory factors in plant response to drought and salt which are the two osmotic stresses seriously affecting plant production. In our previous studies, GmNAC085 was confirmed as a drought-responsive gene in shoots and roots of soybeans. In this study, expression of GmNAC085 under osmotic stresses was examined in drought-tolerant soybean DT51. 12-day-old plants were dehydrated or treated with salt for 0 h, 2 h and 10 h. Our results shown that under dehydration, the expression of GmNAC085 significantly increased in both shoots and roots, especially in shoots. More specifically, its expression was elevated 30-fold in shoots and 5-fold in roots at 2 h; at 10 h, its expression was elevated 260-fold in shoot and 8-fold in root of DT51; in MTD720, expression was elevated 15-fold and 28-fold in root, 499-fold and 494-fold in shoot tissues at 2h and 10h, respectively. Similarly, under salt treatment at 2h and 10h, the expression of GmNAC085 was up-regulated in both shoots and roots. The expression of GmNAC085 was elevated 35-fold and 656-fold in shoots, 2-fold and 14-fold in root of DT51, respectively; meanwhile, in MTD720, expression was elevated 10-fold and 377-fold in shoots, 5-fold and 26-fold in roots. Therefore, GmNAC085 was considered to be not only drought-responsive but also abiotic stress-responsive. GmNAC085 is a potential gene for genetic engineering to improve stress tolerance in soybean and other crops.